Ethical and Philosophical Considerations for Gain-of-Function Policy: The Importance of Alternate Experiments - Evans, Nicholas Greig (Frontiers in Bioengineering and Biotechnology, 2018)
The Framework for Guiding Funding Decisions about Proposed Research Involving Enhanced Potential Pandemic Pathogens contains a series of principles for governing the funding and conduct of Gain of Function (GOF) research resulting in the creation of potential pandemic pathogens (PPPs). In this article, I address one of these principles, governing the replacement of GOF research with alternate experiments. I argue that the principle fails to address the way that different experiments can promote the same values as those promoted by GOF research resulting in PPPs. I then address some objections to this claim, and provide policy recommendations moving forward.